PTU-195 Robotic colorectal surgery: a single centre experience of first 100 consecutive cases. (22nd June 2015) - Ahmed, J; Abbass, H; Stefan, S; Flashman, K; Khan, J; Parvaiz, A
Abstract : Introduction: Robotic surgery has gained momentum in various surgical disciplines. The provision of a stable platform with excellent 3D view and improved access which enhances surgical capabilities for precise dissection in a narrow surgical field has made it an attractive option for colorectal surgeons. The aim of this study was to present the clinical outcomes of first 100 robotic colorectal procedures performed in a single centre between May 2013 and January 2015. Method: Prospectively collected data related to 100 consecutive patients who underwent robotic colorectal surgery was analysed for surgical and oncological outcomes. Results: There were 68 male patients (68%) with a median age of 68 years (range 24–92). 15% of patients had neoadjuvant chemoradiotherapy. 23% patients had BMI >30. Rectal resections were performed in 95 patients (85 for cancer and 10 for colitis). Other procedures included right hemicolelctomy (1%), Hartmanns procedure (2%) and left hemicolectomy (2%). Median operating time was 240 min (range- 128–456). whilst median blood loss was 10 mls (range 0–200). There was no conversion to open or laparoscopy and no intra-operative complications. Median length of stay was 7 days (range- 3–48). 30 days mortality was nil whilst readmission rate was 8%. 2 patients had anastomotic leak and 2 had small bowel obstruction, requiring reoperation (4%). 42 patients had tumour stage T3 or 4. R0 resection was achieved in 95% cases and median of lymph node harvest was 16 (range 6–43). Conclusion: Robotic colorectal surgery is safe and feasible. This approach shows promising clinical and oncological outcomes and may become an integral part of colorectal surgery in future. Disclosure of interest: None Declared.